Recent development of photoacoustic imaging in dentistry: A review on studies over the last decade - Atika Windra Sari; Rini Widyaningrum; Andreas Setiawan; Mitrayana (Saudi Dental Journal)
Background: This work performs a literature review of photoacoustic imaging (PAI) in dentistry and discusses the development of PAI in relation to oral health. Methods: A search method was used to locate papers published between 2011 and 2023 in Google Scholar and PubMed databases, and 25 studies were selected. Reports on PAI in dentistry were included. Articles not written in English or whose full text could not be accessed were excluded. The remaining publications were checked and evaluated to determine whether they contain supportive materials for PAI in dentistry. Results: The majority of articles about PAI in dentistry are associated with caries studies. Photoacoustic microscopy is the most commonly utilized PAI system. PAI studies generally focus on ex-vivo investigations using extracted human teeth. The acoustic signal obtained from carious teeth is greater than that obtained from normal teeth. In addition to imaging oral soft tissues from animal models and the periodontal pocket depth in human volunteers, PAI is applied to evaluate dental implants and oral biofilms. Conclusion: There have been numerous investigation on PAI in dentistry, but it is not yet applicable in dental practice. In the future, PAI studies are expected to contribute to the invention of an alternative non-ionizing imaging technology that is comfortable for patients, user friendly, and capable of providing reliable information at a reasonable cost.